Revision of the Neotropical Stiletto Fly Genus Notiothereva Metz & Irwin (Diptera: Therevidae: Therevinae) - Webb, Donald W. (Zootaxa, 2005)
The Neotropical genus Notiothereva Metz and Irwin is revised to include six species. Notiothereva argentina spec. nov. and N. aurea spec. nov. are described, while Notiothereva ruficornis (Kröber) is synonomized with N. albiventris (Philippi). Each species is described or redescribed with illustrations of their genitalia, a key to their identification, and a map of their distribution.